2010
DOI: 10.1126/scitranslmed.3000391
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Prophylaxis with Oral Truvada Protects Macaques from Rectal SHIV Infection

Abstract: HIV continues to spread globally, mainly through sexual contact. Despite advances in treatment and care, preventing transmission with vaccines or microbicides has proven difficult. A promising strategy to avoid transmission is prophylactic treatment with antiretroviral drugs before exposure to HIV. Clinical trials evaluating the efficacy of daily treatment with the reverse transcriptase inhibitors tenofovir disoproxil fumarate (TDF) or Truvada (TDF plus emtricitabine) are under way. We hypothesized that interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
185
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(200 citation statements)
references
References 37 publications
11
185
1
1
Order By: Relevance
“…However, macaques exposed to an SIV isolate carrying the TDF resistance mutation (K65R) were not protected by TDF, which suggests PrEP may be less effective against ARV-resistant viruses (19). Substantial reductions in viremia and blunted acute viremias (up to 2log 10 reduction) have been observed in a patient failing Truvada and in macaques failing PrEP with FTC, Truvada, or a CCR5 inhibitor (17,18,(20)(21)(22). These results suggest that even when PrEP does not prevent infection it may, by reducing viral load and/or reducing CD4 + T-cell depletion, help preserve immune function that could attenuate the course of HIV infection (21).…”
Section: (Materials and Methods)mentioning
confidence: 99%
“…However, macaques exposed to an SIV isolate carrying the TDF resistance mutation (K65R) were not protected by TDF, which suggests PrEP may be less effective against ARV-resistant viruses (19). Substantial reductions in viremia and blunted acute viremias (up to 2log 10 reduction) have been observed in a patient failing Truvada and in macaques failing PrEP with FTC, Truvada, or a CCR5 inhibitor (17,18,(20)(21)(22). These results suggest that even when PrEP does not prevent infection it may, by reducing viral load and/or reducing CD4 + T-cell depletion, help preserve immune function that could attenuate the course of HIV infection (21).…”
Section: (Materials and Methods)mentioning
confidence: 99%
“…Des essais, dont un en France (essai ANRS IPERGAY), évaluent actuellement l'efficacité d'une PrEP orale intermittente consistant à prendre des comprimés, non pas en continu, mais avant et après l'exposition au risque VIH. Des études chez l'animal ont déjà validé la preuve de concept de cette posologie [47]. L'intermittence pourrait augmenter l'adhésion des personnes à cette stratégie, améliorer la tolérance et également réduire les coûts qu'entraînerait une prise de la PrEP en continu.…”
Section: Revuesunclassified
“…However, the high drug doses and subcutaneous drug delivery might have overestimated efficacy in both studies. More recent work using human equivalent doses of Truvada showed that macaques can be protected from rectal SHIV infection by several PrEP modalities, including a single oral dose given 1 -7 d before exposure, followed by a second dose 2 h after exposure (Garcia-Lerma et al 2010). Exposure-driven prophylactic modalities initiated around the time of exposure also maintained protection.…”
Section: Preclinical Research In Animal Modelsmentioning
confidence: 99%